2016
DOI: 10.7717/peerj.2679
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of a cold-adapted endo-1, 4-β-glucanase from Citrobacter farmeri A1, a symbiotic bacterium of Reticulitermes labralis

Abstract: BackgroundMany biotechnological and industrial applications can benefit from cold-adapted EglCs through increased efficiency of catalytic processes at low temperature. In our previous study, Citrobacter farmeri A1 which was isolated from a wood-inhabiting termite Reticulitermes labralis could secrete a cold-adapted EglC. However, its EglC was difficult to purify for enzymatic properties detection because of its low activity (0.8 U/ml). The objective of the present study was to clone and express the C. farmeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The optimum temperature of EG-PY2 was lower than that of CelX isolated from a deep sea-bacterium Pseudoalteromonas sp. and of EglC isolated from a symbiotic bacterium Citrobacter farmeri (Zeng et al 2006;Bai et al 2016). The cold activity pattern of EG-PY2 did not change markedly between 20 and 50 o C, which is similar to those reported for reasons of the endoglucanases Cel9P, EG5C and PgluE8 from Paenibacillus sp.…”
Section: Properties Of Eg-py2supporting
confidence: 70%
“…The optimum temperature of EG-PY2 was lower than that of CelX isolated from a deep sea-bacterium Pseudoalteromonas sp. and of EglC isolated from a symbiotic bacterium Citrobacter farmeri (Zeng et al 2006;Bai et al 2016). The cold activity pattern of EG-PY2 did not change markedly between 20 and 50 o C, which is similar to those reported for reasons of the endoglucanases Cel9P, EG5C and PgluE8 from Paenibacillus sp.…”
Section: Properties Of Eg-py2supporting
confidence: 70%
“…Further, we conducted the SDS-PAGE analysis under denaturing conditions, and the molecular weight of the purified recombinant BpEG was estimated to be 60 kDa ( Figure 3A). The molecular weights of the endo-1,4-β-glucanases from other species, namely Rhizopus oryzae (Murashima et al, 2002), Citrobacter farmeri A1 (Bai et al, 2016), and Ganoderma lucidum (Liu et al, 2016), were previously reported.…”
Section: Heterologous Expression Of Recombinant Bpegmentioning
confidence: 74%
“…The sequencing analysis of the above-obtained recombinant BpEG fragments using an automatic protein sequencer showed us the conserved domains AIRVYLWAGM and VPGLGVTLLP. These conservative fragments exhibited high similarity with the endo-1,4-β-glucanases sequences of E. coli (Park and Yun, 1999) and Citrobacter farmeri A1 (Bai et al, 2016), which belong to GH 8.…”
Section: Western Blot Analysis and Identification Of The Partial Peptmentioning
confidence: 92%
See 1 more Smart Citation
“…Some of the cellulases previously reported and applied on the market were mesophilic and thermophilic enzymes [5][6][7][8][9][10][11][12], while a few cold-adapted cellulases have been studied, such as CaCel from Cryptopygus antarctica [13], CelG from Fibrobacter succinogenes S85 [14], CelM of Pseudomonas sp. MM15 [15], etc. Compared with medium-temperature cellulase, cold-active enzymes have a unique role in industrial production and food processing [16].…”
Section: Introductionmentioning
confidence: 99%